STABILIZED DEPRECIATION. - Sweeney, Henry W. (The Accounting Review, 1931)
Abstract Methods of the usual, present, orthodox type are unstabilized because they ignore all lack of uniformity in the value content of the measuring-unit in which the depreciation is expressed. If, for instance, a building cost $50,000 in 1910 and had an expected life of twenty years, with no final scrap value, the depreciation, according to the customary, straight-line method would be the unstabilized one of $2,500 for each of the twenty years regardless of whether, as thus stated in the dollar value of 1910, it was equivalent to $2,500 in the average general price level of each of such twenty pars. Orthodox calculation of depreciation thus assumes that the original cost, when distributed as depreciation over subsequent periods, will continue to have the same economic significance as it had when incurred-or, in other words, that the monetary standard of measurement remains stable in value. The chief merit of such an unstabilised depreciation method is the greater ease in theory and application resulting from the assumption of a higher degree of simplicity in the measurement of facts than is actually there.